OP24 Chronic hepatitis B virus infection in the UK: a multicentre study of clinical and virological characteristics. (16th November 2010) - Fries, L; Rodger, A; Ijaz, S; Moreea, S; Bathgate, A; Wong, T; Rosenberg, W; Bassendine, M; Mills, P; Ryder, S; Mutimer, D; Dusheiko, G; et al.
Abstract : Introduction: Hepatitis B virus (HBV) infection is an important health problem in the UK where 180 000 to 326 000 people are estimated to be chronic carriers of the virus and at increased risk of cirrhosis and hepatocellular carcinoma. Aim: To establish a national register of chronic HBV patients for long-term follow-up to provide comprehensive data on demographic, clinical, and virological characteristics of chronic HBV infection in the UK. Method: Adult patients with chronic HBV infection (HBsAg positive >6 months) under active follow-up in 15 UK liver centres were eligible. Patient recruitment commenced in February 2007. Demographic and clinical data were recorded for all patients. Serum samples were collected on a subset of patients to determine HBV genotype and presence of mutations by sequencing. Results: 1147 patients have been registered. Their mean age was 43±13 years; 57% were male. The most common ethnicities were Chinese (26%), white (22%) and Pakistani (18%). The majority (81%, 676/831) were born outside the UK primarily in Pakistan (15%), Hong Kong (12%) and China (10%). 22% were HBeAg positive. Cirrhosis was present in 17% of cases that had a liver biopsy (n=447). 63% were HBV antiviral treatment naïve. 33% were currently on treatment of which 53% were on monotherapy primarily with either lamivudine (53%) or entecavir (28%). HBV DNA was currently undetectable in 53% (193/362) of treated subjects. The prevalence of HBV genotypes in those sequenced (n=293) was as follows: A (14%), B (17%), C (18%), D (42.7%), E (8%) and G (0.3%). HBV genotypes differed according to ethnicity (p<0.001): whites were predominantly genotypes A (46%) and D (46%), Chinese genotypes B (44%) and C (46%), black Africans genotypes A (21%) and E (53%) and Pakistanis genotype D (97%). Precore and basal core promoter region mutations (BCP; T1762/A1764) occurred in 45% (127/280) and 15% (42/280) of those tested, respectively. 20% (56/280) of the samples carried both precore and BCP mutations. HBsAg mutations indicative of altered antigenicity and could potentially be involved in vaccine escape were detected in 19% (54/286). Polymerase mutations associated with antiviral resistance were identified in 23% (18/77) (only those currently/previously on treatment). Conclusion: We have established the first nationwide chronic HBV register in the UK. In our study population, chronic HBV infection was predominant in immigrants born in countries with high HBV prevalence. A strong association was found between HBV genotypes and ethnicity. Precore mutations were more common than BCP mutations and one-fifth of those tested carried both mutations. The cross-sectional data have enabled exploration of epidemiological associations with chronic HBV infection, the use of antivirals, molecular typing and emergence of novel resistance strains in clinical practice which may differ from clinical trial results. Prospective follow-up of the cohort will allow further characterisation of long-term outcomes.